Thermodynamic analysis of a non linear lattice - Silva, R. A. S. [UNESP]; Drigo Filho, Elso [UNESP]; Ruggiero, José Roberto [UNESP] (Sociedade Brasileira de Física, 2008)
We investigate an extension of the Perard and Bishop (PB) model. In the studied model we get a harmonic one dimensional lattice chain with an additional Morse potential on site. The rotation and vibration motion of each component of the lattice are considered and the coupling for these motions is introduced by a resonance condition. Thermodynamics and structural properties of the system are explored.
Keywords: Non-linear lattice; Peyrard-Bishop model; Morse potential; Radius of gyration